Continuity and change in Brazil and the Southern Cone: research trends and the library collecions for the Year 2000 - Hartness, Ann ed. (SALALM Secretariat AlbuquerqueUS, 1992)
Looks at social, economic, political and cultural trends and manifestations of change, and their implications for libraries responsible for collecting research materials from the region. Examines recent developments in publishing, bookselling, libraries and information technology.